Study of Rainfall Pattern at Bhubaneswar - Susama sudhishri; S.C.Nayakee (Journal of Soil and Water Conservation, 2022)
Rainfall charts from self-recording rain gauge corresponding to fifteen prolonged and intense storms during the years (1976-1989) were analysed for determination of the rainfall pattern at Bhubaneswar. The pattern of storm is determined by the arrangement of rainfall intensity histogram through dimensionless distribution curve considering as one group. Each group was represented by an average pattern. The representative pattern of each group containing maximum number of storms was considered as the pattern of rainfall at Bhubaneswar. By visual observations, the identical patterns were grouped into five types. The type I contained seven storms, type II four storms, type III two storms, and type IV and V each contained one storm. It was observed that the rainfall pattern at Bhubaneswar is of an advanced type, which brings higher intensities when the infiltration rate is the greatest, thus causes higher runoff peaks.